Tweak : (growing up on methamphetamines) - Sheff, Nic. (New York : Atheneum Books for Young Readers, 2007)
The author details his immersion in a world of hardcore drugs, revealing the mental and physical depths of addiction, and the violent relapse one summer in California that forever changed his life, leading him down the road to recovery.
"Ginee Seo books"--T.p.
Keywords: Sheff, Nic; Drug addicts -- California -- Biography; Drug addicts -- Rehabilitation -- California; Methamphetamine abuse -- California -- Biography